2020
DOI: 10.1136/jmedgenet-2020-106973
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deep sequencing of DNA from multiple tissue types improves the diagnostic rate and reveals a highly diverse phenotype of mosaic neurofibromatosis type 2

Abstract: BackgroundAlthough 60% of patients with de novo neurofibromatosis type 2 (NF2) are presumed to have mosaic NF2, the actual diagnostic rate of this condition remains low at around 20% because of the existing difficulties in detecting NF2 variants with low variant allele frequency (VAF). Here, we examined the correlation between the genotype and phenotype of mosaic NF2 after improving the diagnostic rate of mosaic NF2.MethodsWe performed targeted deep sequencing of 36 genes including NF2 using DNA samples from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…For the first sample of meningioma (meningioma 1), targeted amplicon sequencing of NF2 was performed as previously described (Yuzawa et al, 2016), and the loss of NF2 was identified (Figure 2c). Because complete loss of NF2 is frequent in meningiomas but uncommon as a germline mutation of NF2 (Moyhuddin et al, 2003; Teranishi et al, 2021; Yuzawa et al, 2016), NF2 p.Q65X nonsense mutation was considered an initial postzygotic somatic mutation. Based on the peripheral blood genetic analysis, the patient was genetically diagnosed as a mosaic patient.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the first sample of meningioma (meningioma 1), targeted amplicon sequencing of NF2 was performed as previously described (Yuzawa et al, 2016), and the loss of NF2 was identified (Figure 2c). Because complete loss of NF2 is frequent in meningiomas but uncommon as a germline mutation of NF2 (Moyhuddin et al, 2003; Teranishi et al, 2021; Yuzawa et al, 2016), NF2 p.Q65X nonsense mutation was considered an initial postzygotic somatic mutation. Based on the peripheral blood genetic analysis, the patient was genetically diagnosed as a mosaic patient.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of DNA sequencing and multiplex ligation‐dependent probe amplification for blood and separate tumors has revealed mosaicism in 25%–33% of patients with NF2 (Evans et al, 2020; Moyhuddin et al, 2003). Recent studies have reported higher sensitivity and proportions of predicted mosaicism with 37.7%–59.7% using next‐generation sequencing to detect NF2 alteration with low VAF in patients with mosaic NF2 (Evans et al, 2020; Teranishi et al, 2021). Mosaicism in patients with NF2 has been speculated based on the VAF in the blood DNA or by identical mutations in different tumors in previous reports (Evans et al, 2020; Moyhuddin et al, 2003; Teranishi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations